Microbial community structure during the restoration of Wuliangsuhai sediment (Bangladesh Journal of Botany, 2025)
In this study, the sediment in the process of in-situ restoration was taken as the research object. Based on high-throughput sequencing, microbial community structure in sediment at 2 and 6 months was analyzed. The results showed that the dominant bacterial phyla in the repair process included Proteobacteria, Bacteroidota, Chloroflexi and Desulfobacterota. The dominant phyla of fungi changed from Ascomycota, Basidiomycota and Mortierellomycota to Ascomycota. Thiobacillus is the dominant bacterium in the genus.The dominant strain of fungi has changed from Solicoccozyma and Mortierella to Exophiala. Redundancy analysis showed that COD was the main environmental factor affecting bacterial communities (Proteobacteria and Bacteroidota). TP is the main environmental factor affecting the sediment fungal community. This study provides a theoretical basis for the development of in-situ remediation technology of Wuliangsuhai sediment.Bangladesh J. Bot. 54(3): 645-655, 2025 (September) Special